(untitled) (Journal of Parents and Teachers, 2014)
Mariano Fernández Enguita, a professor of Sociology at the University of Salamanca, is interviewed. His research focuses on social inequality, education and organizations. He explains the difference between the terms multiculturalism, multiculturalism and interculturalism; also in which stage of interculturalism is the Spanish school. Finally, he talks about the next steps of interculturality and how teachers are related to the challenges that the next stages pose.